Before the coffee gets cold - Kawaguchi, Toshikazu, 1971- (Picador, an imprint of Pan Macmillan, 2019)
In a small back alley in Tokyo at a century-old coffee shop rumored to offer patrons the chance to travel back in time, four customers reevaluate their formative life choices.